2017
DOI: 10.2214/ajr.16.16680
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing MRI Logistics: Focused Process Improvements Can Increase Throughput in an Academic Radiology Department

Abstract: Focused process improvements in selecting MRI protocols and scheduling examinations significantly increased throughput in the MRI division, thereby increasing capacity and revenue. Shorter scan and department times may also improve patient experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…In order to optimize the utilization of MRI in the most cost‐efficient manner, most radiology practices attempt to optimize exam protocols and MRI scheduling to minimize wasted time and resources . Typically, these efforts focus on limiting the number of acquired sequences, thereby limiting overall exam time . However, process optimization emphasizes minimizing both waste and variation as key steps in process improvement .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to optimize the utilization of MRI in the most cost‐efficient manner, most radiology practices attempt to optimize exam protocols and MRI scheduling to minimize wasted time and resources . Typically, these efforts focus on limiting the number of acquired sequences, thereby limiting overall exam time . However, process optimization emphasizes minimizing both waste and variation as key steps in process improvement .…”
mentioning
confidence: 99%
“…3 Typically, these efforts focus on limiting the number of acquired sequences, thereby limiting overall exam time. 4 However, process optimization emphasizes minimizing both waste and variation as key steps in process improvement. 5 The impact of exam length variability on scanner utilization, however, is often overlooked in this process.…”
mentioning
confidence: 99%
“…Our study demonstrated ABMR to have a 13% faster overall patient flow rate compared to FPMR. This gain in operational efficiency translates to increased capacity, improved patient access, reduced unit cost, and increased potential for revenue 12,17 growth. ABMR demonstrated a 39% reduction in magnet time compared to FPMR which is postulated to result in better patient care through improved compliance and less image motion artifact especially 10 for patients who suffer from claustrophobia.…”
Section: Discussionmentioning
confidence: 99%
“…The table time for an MRI examination can be divided into three intervals with different value weighting: (a) value-added time (activities that directly benefit patients, primarily the actual image acquisition time), (b) business value-added time (necessary activities that consume time but do not directly influence patient care, such as preparing or cleaning the room), and (c) nonvalue-added time (time lost without activity, such as when the imaging equipment is idle) (6). Investigators have demonstrated that identifying possible inefficiencies and implementing change…”
Section: Optimizing Mri Logisticsmentioning
confidence: 99%